Integrated Neurorehabilitation (INRA) for Children with Cerebral Palsy: Protocol and Case Report on Promoting Neuroplasticity - Maja Roje Novak (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Cerebral palsy (CP) is the commonest cause of physical disability in children, but optimal rehabilitative protocols have yet to be determined, and progress in developing novel interventions has been slow. Neuroplasticity is no longer thought to be fixed in childhood, but instead develops throughout life; however, the best way to exploit the remodeling brain has yet to be determined. The management of CP must, therefore, be multidisciplinary to achieve the best outcomes. The use of nutraceuticals (a food or product with health benefits, or a dietary supplement) in the management of cerebral palsy is less well documented, but there are a few examples of studies examining the use of vitamin supplementation in children with CP,18,19 and children with CP are known to suffer from micronutrient deficiencies and anti-oxidant imbalances. This study presents a novel multimodal integrative medicine protocol for the management of children and adolescents with CP termed Integrated Neurorehabilitation (INRA). The basic INRA protocol combines physical therapy, magnetostimulation, and a nutraceutical regimen to provide endogenous and exogenous neurorestorative stimuli to damaged corticospinal pathways on a background of an optimized neuronal microenvironment. A 13-year-old boy with cerebral palsy was referred to the clinic with severe motor, intellectual, and speech deficits. This study illustrates the protocol with the case of a 13-year-old boy showing marked improvements in gross motor function (GMFM-88 score 82% from 59%), speech (TOM score 3 from 0), and cognition (TOEM score 3 from 1) after four years of therapy. There was also a slight increase in his IQ and a decrease in epileptiform activity on EEG. Epileptiform activity on EEG was reduced. This study describe the protocol in full and the scientific rationale for its implementation. IRNA can be used alongside existing medical and rehabilitative regimens to promote neuroplasticity and synaptogenesis. Further testing of the protocol is required in a prospective clinical trial.